Local Wisdom of Nyangu in Sundanese Society: Source of Local Cultural Character Education Values - Taniady, Vicky; N, Encep Syarief; Ruyadi, Yadi; S, Momod Abdul; Suresman, Edi (QALAMUNA: Jurnal Pendidikan, Sosial, dan Agama, 2025)
This study investigates the local expertise of Nyangu (traditional rice cooking) in the Sundanese community as a source of cultural character education principles, emphasizing health, food security, and moral-social aspects.  The study uses an integrated literature review strategy to synthesis qualitative and quantitative data from many disciplines, including cultural anthropology, education, and nutrition.  Thematic analysis yielded three key findings:  (1) Nyangu boosts health by producing resistant starch, lowering the glycemic index, and lowering the risk of diabetes and obesity compared to modern rice cookers. (2) It incorporates food security through zero-waste practices, repurposing leftovers into traditional meals (e.g., opak, pepes), and demonstrates sustainable resource management in line with the SDGs.  (3) The practice instills moral-social values such as community eating (botram) and food reverence, which promote social cohesiveness and cultural identity. The conclusions underline the importance of Nyangu in sustaining Sundanese history in the face of globalization, with implications for incorporating its values into official and informal education curricula. This integration can potentially strengthen cultural identity, encourage sustainable practices to counter cultural degradation, and call for a legislative framework linking traditional practices with modern educational institutions.